Índice de atividade econômica do município de São Luís - CARNEIRO, Laura Regina (2021)
This master thesis aims to develop a weighted multidimensional index which monitors the economic activity level of São Luís. Its relevance comes from its timeliness, since the number that currently summarizes local economic activity, Municipal GDP, is published annually, with 2 (two) years lag. The statistical method used is Principal Component Analysis (PCA), a multivariate technique aimed at reducing data dimensions, with minimal loss of information, vastly recognized to create indexes. The results achieved allow us to infer that the Economic Activity Index of the municipality of São Luís is a proxy capable of measuring local economic activity.